Humor sebagai Mediasi Konflik Digital: Analisis Wacana Kritis @NUgarislucu - Risa Pramita Wilda Fitria; Nyimas Ma'rifatillah (LAKPESDAM MWCNU Palengaan, 2026)
This study focuses on the X account @NUgarislucu as a representation of the Nahdlatul Ulama (NU) community that employs humor as an alternative discursive practice. The study examines how the discursive structure of humor functions as digital conflict mediation. Data were collected through X advanced search using the operator